2017
DOI: 10.1186/s12905-017-0462-3
|View full text |Cite
|
Sign up to set email alerts
|

Couple’s concordance and discordance in household decision-making and married women’s use of modern contraceptives in Bangladesh

Abstract: BackgroundAlthough a large body of studies documents that women’s autonomy in the household is associated with better reproductive health outcomes, these studies typically examined autonomy only from women’s point of view. The current study employs husband’s and wife’s perspectives together to examine the relationship between the decision-making arrangements in the household and the women’s use of modern contraceptives in Bangladesh.MethodsThe study used the couple dataset of 2007 Bangladesh Demographic and He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 49 publications
2
30
0
1
Order By: Relevance
“…However, providers view concerning young women FP counseling when they come to the health facilities was not considered in this study although evidence indicated as provider related biases hamper young women's access to contraceptive information and services in sub-Saharan Africa. 51 Despite evidence identified considerable disagreement between the couple regarding who exercises more in the household decision-making power, 47 husband's view was not asked in this study. Moreover, responses to the outcome and independent variables measurement might be affected by the recall and social desirability bias.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…However, providers view concerning young women FP counseling when they come to the health facilities was not considered in this study although evidence indicated as provider related biases hamper young women's access to contraceptive information and services in sub-Saharan Africa. 51 Despite evidence identified considerable disagreement between the couple regarding who exercises more in the household decision-making power, 47 husband's view was not asked in this study. Moreover, responses to the outcome and independent variables measurement might be affected by the recall and social desirability bias.…”
Section: Discussionmentioning
confidence: 98%
“…However, many young women in a patriarchal society like Ethiopia, particularly in a rural setting, have lesser decisionmaking power on major household issues due to economic dependence, lesser negotiation skills, and other existing culture. 47 These findings depict the need for strategies that empower young women to develop negotiation skills to choose the number of children they desire and challenge the traditional male dominance that limits their access to contraceptive services. Qualitative studies suggested the importance of factual information that describes the contraceptive methods for young married women in developing countries since most of them are married at an early age with limited knowledge of contraception.…”
Section: Discussionmentioning
confidence: 99%
“…This is not surprising as a mother’s decision to seek care during pregnancy depends, to some extent, on the level of education. Several studies have identified education as a major determinant of maternal health and health seeking behavior [6, 10, 16, 19]. Unfortunately, in developing countries like Ghana, women from poorer household also have lower educational attainments relative to their counterparts from rich households.…”
Section: Discussionmentioning
confidence: 99%
“…20 This definition has been used to guide data collection and analysis in several similar studies. [21][22][23][24]…”
Section: Study Population and Data Sourcementioning
confidence: 99%